For Putin and for Sharia : Dagestani Muslims and the Islamic State - Kaliszewska, Iwona (NIU series in Slavic, East European, and Eurasian studies., 2023)
"This book explores what it means to support Sharia in twenty-first-century North Caucasus. Who are 'the terrorists' in Dagestan and how do they cope with the fight against terrorism?"--